Service Analysis Against Customer Interest at Kremes Chicken Restaurant Mas Rusdi Palu - Sirajuddin Sirajuddin; Ni Gusti Ayu Putu Veni Yulia; Salmiati Salmiati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
In general, the meaning of marketing is marketers' activity to carry out business (profit or non-profit) to meet market needs with goods or services, fix prices, distribute, and promote through the exchange process to satisfy consumers and achieve company goals. From the calculation results obtained by using a simple linear regression model analysis, the correlation coefficient (R) of 0.585 indicates a moderate relationship between the service variable (X) and the customer interest variable (Y), with an R contribution (coefficient of determination) of 0.585 indicating that 58.5% of customer interest is determined by service. Simple linear regression model analysis obtained a Fount of 30.210 with a probability level of 0.000 (significant), and the probability value is much smaller than 0.05. This shows that the service variable (X) has a considerable influence on the customer interest variable (Y) at Kremes Chicken Restaurant Mas Rusdi Palu.